Surface potential shift in MoS2 due to adsorption of H2O - Ganatra, Rudren (2015)
In this thesis, the variation of work function or surface potential of MoS2 due to adsorption of H2O molecules under varying relative humidity conditions is studied in detail. MoS2’s ultra-thin layered structure coupled with the presence of unsaturated d-orbitals from the transition metal molybdenum makes it an appealing candidate for designing gas sensors. In this work, the Kelvin probe force microscopy (KPFM) function of the atomic force microscope (AFM) was used to successfully map the surface potential of MoS2 flakes of varying thicknesses as relative humidity levels are changed within a sealed AFM chamber. The effects of H2O adsorption, desorption, doping and surface potential shift of MoS2 have been studied in detail. After carrying out this study, a deeper understanding of the adsorption mechanism of H2O and MoS2’s surface potential response has been obtained. The KPFM technique is used to obtain the surface work function or surface potential values of MoS2 flakes with the variation of relative humidity levels to study charge-induced material doping due to H2O adsorption on the surface of MoS2. Through this technique, this study was able to quantitatively determine the surface potential response of MoS2 to change in relative humidity levels between RH 10% and RH 70%. The shift in surface potential of was found to be very consistent across sample flakes with different thicknesses and surprisingly showed no noticeable hysteresis effect. Edges were found to possess a lower potential but also followed surface potential variation with humidity. The adsorption mechanism, lack of hysteresis and consistent material response are discussed.